Potere e Regalità dei Duchi di Savoia nella prima Età Moderna: la testimonianza degli Ambasciatori Veneti. - Merlin, Pierpaolo (Studi Piemontesi)
In 16th century the Republic of Venice created an efficient diplomatic network that was active in the most important courts of Europe. Starting from 1560 the Serenissima maintained a resident ambassador at the Savoy court, as it was considered of great political importance. In their relations, all Venetian diplomats underlined the progressive consolidation of the ducal power and tried to explain the causes of this process. The essay focuses on the thoughts of the Venetian ambassadors on the Savoy sovereignty in the period 1560-1613, when the Duchy was ruled by Emmanuel Philibert and Charles Emmanuel I.